2010
DOI: 10.1210/jc.2009-1728
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity of DNA Variants and Double Mutations in Multiple Endocrine Neoplasia Type 2 and Von Hippel-Lindau Syndrome

Abstract: RET p.Tyr791Phe and p.Ser649Leu and VHL p.Pro81Ser are definitely not pathogenic mutations for VHL and MEN 2. Misinterpretation results in irreversible clinical consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 19 publications
2
69
0
2
Order By: Relevance
“…Notably, the A883T mutation that we previously reported ) is associated with MTC only in homozygous subjects, suggesting a low transforming activity of this mutation, which is likely counterbalanced by the normal allele in heterozygous subjects. Other RET mutations, such as Y791F, may also occur more frequently than currently recognised if the development of MTC only occurs in homozygous subjects (Erlic et al 2010). However, although the Y791F mutation seems to have a high prevalence in the normal German population, none of the six new mutations have been detected in the 200 normal subjects examined in this study; thus, this finding excludes the polymorphic nature of our new mutations and makes the possibility of a homozygous condition in children of non-consanguineous parents very unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the A883T mutation that we previously reported ) is associated with MTC only in homozygous subjects, suggesting a low transforming activity of this mutation, which is likely counterbalanced by the normal allele in heterozygous subjects. Other RET mutations, such as Y791F, may also occur more frequently than currently recognised if the development of MTC only occurs in homozygous subjects (Erlic et al 2010). However, although the Y791F mutation seems to have a high prevalence in the normal German population, none of the six new mutations have been detected in the 200 normal subjects examined in this study; thus, this finding excludes the polymorphic nature of our new mutations and makes the possibility of a homozygous condition in children of non-consanguineous parents very unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…At present, these mutations could be considered as allelic variants (41,42). While the phenotype of MEN 2A and 2B is relatively easy to be defined because based on the positive family history and/or the association with other endocrine and non-endocrine diseases (7,15,26), the definition of FMTC is more challenging because it may be thought that the other endocrine neoplasms are not yet developed at the time of FMTC diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…2,18 However, the c.340 C 5G > C mutation, which was associated with VHL type 1B disease, 2,18 has always been disputed because some researchers suggest that it is a benign polymorphism. 19,20 Our in silico analysis also revealed that it did not affect the splicing site alteration. The other missense mutation, c.256C > T (p.P86S), was previously reported in VHL type 1 or type 2B patients.…”
Section: Discussionmentioning
confidence: 63%